SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-3218
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous OH- and Formaldehyde-LIF Measurements in an HCCI Engine

Abstract: Simultaneous OH-and formaldehyde LIF measurements have been performed in an HCCI engine using two laser sources working on 283 and 355 nm, respectively. Two ICCD camera systems, equipped with long-pass filters, were used to collect the LIF signals. The simultaneous images of OH and formaldehyde were compared with heat-release calculated from the pressure-trace matching the cycle for the LIF measurements.The measurements were performed on a 0.5 l singlecylinder optical engine equipped with port-fuel injection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…Hultqvist et al [82] showed cool-flame emission spectra from iso-octane/nheptane HCCI combustion and discussed that these spectra originated from the presence of formaldehyde (HCHO). LIF studies have shown how HCHO and OH species are present within the 'cool' flame period and subsequent 'hot' combustion [84][85][86]. The absence of carbon atoms, and thus HCHO, from the in-cylinder mixture of a hydrogen HCCI engine means that a totally different mechanism of autoignition is in operation and that OH generation would be very different from that of hydrocarbon fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Hultqvist et al [82] showed cool-flame emission spectra from iso-octane/nheptane HCCI combustion and discussed that these spectra originated from the presence of formaldehyde (HCHO). LIF studies have shown how HCHO and OH species are present within the 'cool' flame period and subsequent 'hot' combustion [84][85][86]. The absence of carbon atoms, and thus HCHO, from the in-cylinder mixture of a hydrogen HCCI engine means that a totally different mechanism of autoignition is in operation and that OH generation would be very different from that of hydrocarbon fuels.…”
Section: Introductionmentioning
confidence: 99%
“…With varying levels of complexity of both equipment and technique, they have been applied extensively by many researchers in SI and CI engines for a long period of time [11,12]. For CAI, many researchers have successfully applied PLIF techniques to capture fluorescence of OH and formaldehyde to analyse the autoignition and combustion process [13][14][15]. Application of simpler techniques which do not rely on laser illumination and doped fuels for imaging combustion can allow for more realistic engine conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the low-temperature reactions (cool flames) and the early phase of the main heat release in an HCCI engine can be investigated by probing the formation and consumption of formaldehyde. Conventional planar laser induced fluorescence from formaldehyde, i.e., with one image captured per engine cycle, has been used earlier in investigations of the Controlled Auto Ignition (CAI) combustion concept [11] and for characterization of HCCI combustion [12,13,14]. In the latter publication it was reported how the concentration of formaldehyde increased as the Low Temperature Reactions (LTR) progressed.…”
Section: K Lombaertmentioning
confidence: 99%